critical approach to the speculative imaginations of post-humanism: critical approach to the speculative imaginations of post-humanism - CONTRERAS, Fernando R.; IBANEZ BUENO, Jacques (Utopía y Praxis Latinoamericana, 2021)
This study addresses a theoretical current born between the mythical narrative and the science that proposes the renewal of the human condition. The conceptual consolidation of post-humanism arises from new expectations about the prosperity, well-being and flourishing of a promising future for our world. This article explores post-humanist speculation igniting the scientific and technological triumphs of this century. Among the most characteristic features of this doctrine we highlight the human emancipation of the errors of modernity, the biotechnical control of life or the moral aspiration of bioethics.